Comparison of speech intelligibility and quranic recitation proficiency in Malay cleft palate patients / Siti Nur Nabihah Zainul Abidin - Siti Nur Nabihah, Zainul Abidin (2019)
Speech intelligibility is the most important parameter in determining the success of cleft palate repair. Previous studies have shown that adequate speech intelligibility can be achieved after primary palatoplasty. In Muslim Malay population, there is additional requirement to read Quran proficiently. The aim of this study is to assess perceptual intelligibility of speech and proficiency of Quranic recitations and to compare if there are differences between the two. Data collection was done on 30 patients clinically and by recording speech samples while these patients were reading on a Malay passage and first verse of Holy Quran. Both samples were assessed by authors using assessment form adapted from Cleft Audit Protocol for Speech –Augmented and Quranic Assessment Form adapted from the Malaysian Ministry of Education’s learning module. Result showed that 100% of the patients have understandable speech however only 60% of these patients were able to at least recite Quran fluently with adherence to the Rules of Tajwid. Statistical analysis revealed significant correlation between these two parameters with P-value <0.001. The reported speech intelligibility and Quranic recitation result provide important prognostic reference information not just to the professionals in cleft team but parents and Quranic teachers as well